Effect of dilution of both A-and B-sites on the multiferroic properties of spinal Mott insulators - Shahi P.; Singh R.K.; Singh R.K.; Kumar S.; Tiwari A.; Tripathi A.; Saha J.; Patnaik S.; Ghosh A.K.; Chatterjee S. (My University, 2025)
The structural, magnetic, electrical and transport properties of FeV2O4, by doping Li and Cr ions in A and B sites, respectively, have been studied. Dilution of the A site by Li doping decreases the V-V distances which in effect increases the A-V coupling. This increased coupling enhances the ferrimagnetic ordering temperature and reduces the ferroelectric transition temperature. Furthermore, since Li is non-magnetic the A-V coupling is also decreased. The increase in A-V coupling dominates over the decrease in A-V coupling with Li doping. On the other hand, Cr doping increases the ferrimagnetic ordering temperature but does not alter the ferroelectric transition temperature, which is due to the fact that the polarization originates from the presence of almost non-substituted regions. © 2015 IOP Publishing Ltd.